Audiovisual Media Increases Stunting Prevention Knowledge Among Pregnant Women in The Working Area of Wani Health Center: Pretest, Posttest 1 dan Posttest 2 - Taqwin Taqwin; Mercy Joice Kaparang; Fitri Wahyuningtias; Kadar Ramadhan (Poltekkes Kemenkes Palu, 2023)
Health education about stunting prevention using audiovisual media has never been done for pregnant women in the working area of the Wani Health Center. This study aims to Analyzing the effect of health education through audiovisual media on stunting prevention knowledge among pregnant women in the working area of the Wani Health Center. This study is a pre-experimental study with a one-group pretest posttest design. The population is all pregnant women in four villages in the working area of the Wani Donggala Health Center, Central Sulawesi. The sample consist of 43 respondents. The instruments used were pretest, posttest 1 and posttest 2 questionnaires, with 21 statement numbers. Pre, post 1 and post 2 data collection was carried out at the village office and auxiliary health centers in four villages. Health education materials through audiovisual media is related to stunting prevention. Audiovisual is self-made using animation with a duration of 8 minutes and 12 seconds. Univariate analysis is the frequency distribution and bivariate with the Friedman test. The results showed that the average value of the pretest: 52.18, posttest 1: 71.722 and posttest 2: 90.86. Friedman test obtained a value of ρ 0.000 (<0.05). The conclusions is health education through audiovisual media in posttest 2 significantly increases knowledge of stunting prevention in pregnant women. It is hoped that health workers will increase the use of audiovisual media as a preventive effort to prevent stunting.